(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In recent years, the field of education has increasingly embraced individualized pedagogical technologies to cater to diverse learner needs and enhance educational outcomes. This article explores the mechanisms underlying the implementation of individualized learning technologies, examining their theoretical foundations, practical methodologies, and effectiveness. By addressing individual learner differences through tailored instructional strategies, educators can optimize learning experiences and outcomes. The discussion draws on various studies and insights from educational theorists, providing a comprehensive overview of individualized learning technologies.